2005
DOI: 10.1002/adfm.200500036
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Crystal Growth of Stilbazolium Derivatives for Second-Order Nonlinear Optics

Abstract: A series of ionic stilbazolium salts with benzenesulfonates with different substituents in the para position have been synthesized. Single crystals of 4‐N,N‐dimethylamino‐4′‐N′‐methylstilbazolium p‐methoxybenzenesulfonate (DSMOS) were successfully grown in methanol solution by slow cooling. X‐ray studies revealed that DSMOS crystallized in the triclinic space group P1 with its molecular dipoles perfectly aligned in one direction—favorable for large nonlinear optical and electro‐optical effects. Kurtz powder te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 13 publications
3
108
0
Order By: Relevance
“…Since similar crystal structures have been found for SHGactive DAST derivatives, their crystal structures might be classified into several groups, e.g., Cc group for 2a, 2b, 2d, 2e, and 2m and P2 1 group for 2j and 3h. It has already recognized that complete parallel alignment of cations will give maximum second-order NLO performance of the cation in macroscopic scale [29], and DAST derivatives with space group P1 have been recently reported, i.e., DAS p-methoxybenzenesulfonate [20] and 2k [21]. For terahertz-wave generation using single crystals of DAST derivatives by DFG, generated terahertz-waves in some ranges are attenuated because of self-absorption due to the intra-or inter-molecular vibrations.…”
Section: Article In Pressmentioning
confidence: 99%
“…Since similar crystal structures have been found for SHGactive DAST derivatives, their crystal structures might be classified into several groups, e.g., Cc group for 2a, 2b, 2d, 2e, and 2m and P2 1 group for 2j and 3h. It has already recognized that complete parallel alignment of cations will give maximum second-order NLO performance of the cation in macroscopic scale [29], and DAST derivatives with space group P1 have been recently reported, i.e., DAS p-methoxybenzenesulfonate [20] and 2k [21]. For terahertz-wave generation using single crystals of DAST derivatives by DFG, generated terahertz-waves in some ranges are attenuated because of self-absorption due to the intra-or inter-molecular vibrations.…”
Section: Article In Pressmentioning
confidence: 99%
“…Slow cooling technique was adapted for the growth of bulk crystals. [20] First we prepared saturated solution of DSTMS in methanol at 35-40°C. Spontaneous nucleation could be observed after cooling down the saturated solution.…”
Section: Crystal Growth and X-ray Crystallographic Studymentioning
confidence: 99%
“…It has already been demonstrated that varying the counter-ion to optimize the crystal packing and orient the dipoles as parallel as possible is an effective molecular engineering strategy to develop ionic organic crystals with non-centrosymmetric structure. [17][18][19][20] Using this approach, we have reported the synthesis and crystal growth of DSNS (4-N,N-dimethylamino-4′-N′-methyl-stilbazolium 2-naphthalenesulfonate)-a promising DAST derivative with perfectly aligned chromophores, leading to a 50 % higher nonlinearity in the crystalline powder than DAST. [21] However, only very small crystalline needles of DSNS with a diameter of less than 100 lm could be grown.…”
Section: Introductionmentioning
confidence: 99%
“…[12]. It was found that MP2 method gives the best agreement for calculated structures with X-ray crystallographic data [22]. At the same time, first excited state properties and NLO response calculated using geometries optimized by Hartree-Fock (HF) and MP2 approaches give results close to each other.…”
Section: Computational Detailsmentioning
confidence: 90%